RESEARCH OF THE FACTORS DETERMINING METALLURGICAL OUTPUT AT MELTING OF DISPERSE ALUMINUM MATERIALS - G. V. Dovnar; A. A. Andrits (Литьë и металлургия, 2005)
The results of investigations of metallurgical output at melting of different dispersed aluminum materials are given. The factors, determining the waste of metal at remelting of scrap, are established. The ways of increase of degree of metal extraction from dispersed burden are shown.